MODL-11. NOVEL IMMUNOTHERAPY MODEL IN AGGRESSIVE PEDIATRIC H3K27M MUTANT GLIOMAS WITH INDUCIBLE TGFBR2 AND LAG3 EXPRESSION. (14th November 2022) - Ljubimov, Vladimir; Linesch, Paul; Sabet, Sara; Krutikova, Viktoria; Mehdikhani, Shaunt; Pacheco, David Rincon Fernandez; Danielpour, Moise; Breunig, Joshua
Abstract: INTRODUCTION: Gliomas are considered immunologically "cold" tumors that mask themselves from the immune system. Immunotherapy, a breakthrough for cancer treatment, remains inefficient for gliomas. H3K27M mutant diffuse midline glioma has poor survival. Using our innovative mosaic analysis with dual recombinases technology (Cell 2019), we further created a novel murine model of H3K27M glioma with an inducible expression of LAG3 and TGFBR2 to make the tumor recognizable by the immune system. This allows studying molecular mechanisms of "perfect" immunotherapy in pediatric gliomas with histone H3.3 mutations. METHODS: To make a novel murine model, H3K27M plasmids with doxycycline-inducible expression for TGFBR2 and LAG3 were designed, sequenced, and replicated. For in vitro validation, murine neuronal stem cells were nucleofected with these plasmids, grown and sorted. Doxycycline was added to the experimental group in vitro to induce expression. The plasmids were then electroporated into neonatal MGMT mice (n=21) of both genders. Control mice were used on a standard diet (n=9) and experimental mice (n=12) were given doxycycline in food to induce TGFBR2 and LAG3 expression in vivo . Mice were followed up for survival. RESULTS: Plasmid sequencing validation demonstrated their high purity. In vitro nucleofected neuronal stem cells showed significant increase in TGFBR2 and LAG3 expression by immunofluorescent staining after addition of doxycycline. The mouse survival study showed a significant benefit with treatment group surviving 46% longer (135 ± 41.9 days vs. 92.6 ± 32.7 days in the control group, p=0.030). Conclusion and Future Directions: We have successfully modified H3K27M glioma to have inducible expression of TGFBR2 and LAG3 to simulate "perfect" immunotherapy. The survival study showed a significant survival benefit. The development of organoid transplants for more uniform testing and next-generation sequencing is ongoing. This can lead to the emergence of novel immune therapies and uncover novel mechanisms of tumor response to treatment.